SHP2 Is Required for BCR-ABL1-Induced Hematologic Neoplasia - Gu, Shengqing (Leukemia, 2017)
BCR-ABL1-targeting tyrosine kinase inhibitors (TKIs) have revolutionized treatment of Philadelphia chromosome-positive (Ph(+)) hematologic neoplasms. Nevertheless, acquired TKI resistance remains a major problem in chronic myeloid leukemia (CML), and TKIs are less effective against Ph(+) B-cell acute lymphoblastic leukemia (B-ALL). GAB2, a scaffolding adaptor that binds and activates SHP2, is essential for leukemogenesis by BCR-ABL1, and a GAB2 mutant lacking SHP2 binding cannot mediate leukemogenesis. Using a genetic loss-of-function approach and bone marrow transplantation (BMT) models for CML and BCR-ABL1(+) B-ALL, we show that SHP2 is required for BCR-ABL1-evoked myeloid and lymphoid neoplasia. Ptpn11 deletion impairs initiation and maintenance of CML-like myeloproliferative neoplasm, and compromises induction of BCR-ABL1(+) B-ALL. SHP2, and specifically, its SH2 domains, PTP activity and C-terminal tyrosines, is essential for BCR-ABL1(+), but not WT, pre-B cell proliferation. The MEK/ERK pathway is regulated by SHP2 in WT and BCR-ABL1(+) pre-B cells, but is only required for the proliferation of BCR-ABL1(+) cells. SHP2 is required for SRC family kinase (SFK) activation only in BCR-ABL1(+) pre-B cells. RNAseq reveals distinct SHP2-dependent transcriptional programs in BCR-ABL1(+) and WT pre-B cells. Our results suggest that SHP2, via SFKs and ERK, represses MXD3/4 to facilitate a MYC-dependent proliferation program in BCR-ABL1-transformed pre-B cells.